A Solomon Link through an Interwoven Molecular Grid1. (8th May 2015) - Beves, Jonathon E.; Danon, Jonathan J.; Leigh, David A.; Lemonnier, Jean‐François; Vitorica‐Yrezabal, Iñigo J.
Abstract A molecular Solomon link was synthesized through the assembly of an interwoven molecular grid consisting of four bis(benzimidazolepyridyl)benzthiazolo[5, 4‐d]thiazole ligands and four zinc(II), iron(II), or cobalt(II) cations, followed by ring‐closing olefin metathesis. NMR spectroscopy, mass spectrometry, and X‐ray crystallography confirmed the doubly interlocked topology, and subsequent demetalation afforded the wholly organic Solomon link. The synthesis, in which each metal ion defines the crossing point of two ligand strands, suggests that interwoven molecular grids should be useful scaffolds for the rational construction of other topologically complex structures.